Mobile Phone-based Multimedia Application Could Improve Maternal Health in Rural Southwestern Uganda: Mixed Methods Study - Musiimenta, Angella; Tumuhimbise, Wilson; Mugyenyi, Godfrey Rwambuka; Katusiime, Jane; Atukunda, Esther Cathyln; Pinkwart, Niels (Online Journal of Public Health Informatics, 2020)
Background: Reducing maternal and infant mortality rates remains challenging. Illiteracy, lack of reliable information, long distances to health centers continue to limit access to quality maternal healthcare in Uganda. Mobile health technologies could be promising affordable strategies for enhancing access to maternal health services. However, there is lack of studies assessing the experiences of illiterate rural pregnant women regarding these technologies. Objective: To explore how illiterate pregnant women perceive a maternal health mobile application composed of tailored video and audio messages, appointment reminders and calling function. Methods: We purposively sampled illiterate pregnant women initiating antenatal care at Mbarara Regional Referral Hospital. We carried out three focus group discussions with 14 women to elicit information on perceptions of the proposed mobile phone based multimedia application. We used STATA 13 to describe study participants and their preferences. Results: Pregnant women anticipated that intervention would enhance maternal health by reminding them to attend antenatal appointments, enabling transport cost and time saving, providing tailored information that is easy to understand, and recall. However, financial constraints and phone sharing would limit the functionality. Conclusion: Mhealth application may provide acceptable and affordable alternative approaches to providing maternal health services, especially in settings where face-to-face approaches are challenging.
Keywords: Mobile health technologies; Maternal health; Illiterate women; videos/audios; Multimedia; Appointment reminders